Competitive solvent-molecule interactions govern primary processes of diphenylcarbene in solvent mixtures - Johannes Knorr (Nature Portfolio, 2016)
Photochemistry in solution often involves coexisting reaction channels that may comprise intermediates capturing a solvent molecule. Here, the authors show for one of the most reactive species, diphenylcarbene, that the decision-maker is not the nearest solvent molecule but its neighbour.